ADAPTASI KOSAKATA BAHASA BALI DALAM BAHASA MELAYU LOLOAN BALI - Putu, Anak Agung; Nyoman Seri, Ni Luh; Suparwa, I Nyoman (LITERA, 2015)
Abstract This study aims to describe processes and domains of vocabulary borrowing, word categories, and phonological dynamics in the Loloan Malay language in Bali. The data were collected through participant observations and were analyzed using the generative phonological theory. The results of the study are as follows. First, the Loloan Malay language borrows Balinese vocabulary through two processes, namely adoption and adaptation. Second, the borrowing of Balinese vocabulary in terms of seven universal cultural elements covers the domains of livelihood system, technology, knowledge system, organization, and arts. Third, the borrowing of Balinese vocabulary in terms of word categories occurs in: (a) nouns, pronouns, and numerals; (b) verbs; and (c) adjectives. Fourth, the borrowing of Balinese vocabulary results in the phonological dynamics in the Loloan Malay language. Keywords: borrowing domains